2014
DOI: 10.5713/ajas.14.0330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bacillus amyloliquefaciens</i>-based Direct-fed Microbial on Performance, Nutrient Utilization, Intestinal Morphology and Cecal Microflora in Broiler Chickens

Abstract: The present study was conducted to evaluate the effect of the dietary supplementation of Bacillus amyloliquefaciens-based direct-fed microbial (DFM) on growth performance, nutrient utilization, intestinal morphology and cecal microflora in broiler chickens. A total of two hundred and eighty eight 1-d-old Arbor Acres male broilers were randomly allocated to one of four experimental treatments in a completely randomized design. Each treatment was fed to eight replicate cages, with nine birds per cage. Dietary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 27 publications
9
90
0
5
Order By: Relevance
“…can stimulate the differentiation and proliferation of intestinal epithelial cells and improve nutrient utilization (Artis et al, 2008;Wells et al, 2011;Duerr et al, 2012). Lei reported that broilers receiving a direct-fed microbial based on Bacillus amyloliquefaciens significantly increased crypt depth and villus height to crypt depth ratio in the duodenum, jejunum, and ileum (Lei et al, 2015). Similarly, in broilers fed diets with 200 mg/kg Bacillus coagulans, an increase in V/C ratio was also observed (Lin et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…can stimulate the differentiation and proliferation of intestinal epithelial cells and improve nutrient utilization (Artis et al, 2008;Wells et al, 2011;Duerr et al, 2012). Lei reported that broilers receiving a direct-fed microbial based on Bacillus amyloliquefaciens significantly increased crypt depth and villus height to crypt depth ratio in the duodenum, jejunum, and ileum (Lei et al, 2015). Similarly, in broilers fed diets with 200 mg/kg Bacillus coagulans, an increase in V/C ratio was also observed (Lin et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…Lei reported that the dietary inclusion of spores of a lactobacillus improved the conversion ratio and reduced mortality and culling rate of broilers (Lei et al, 2015). Lactobacilli improve calcium and phosphorus utilization, and lactic acid promotes the transformation of pepsinogen into protease, stimulating the peristalsis of the small intestine to enhance nutrient digestion (Ma et al, 2014;Giang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis has been used as a feed additive to improve the microorganismal environment in the intestine18. We weighed the chickens after they developed immunity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Resultado semelhante também foi observado por Giannenas et al (2010) após adição do cogumelo Agaricus bisporus à dieta que não promoveu efeitos tróficos na mucosa intestinal de frangos de corte, embora tenha favorecido a microbiota intestinal. Já Lei et al (2015) observaram aumento na altura das vilosidades intestinais a partir dos 21 dias de idade ao adicionarem Bacillus amyloliquefaciens à dieta como alternativa ao uso de melhoradores do crescimento na prevenção de enfermidades.…”
Section: Resultsunclassified